Between the physical and the transcendent: In the space of Olesʹ Ulianenko’s prose - Pastukh, Taras (Poznańskie Studia Slawistyczne, 2024)
The review is dedicated to considering the collective book Between the Apocalypse and Melancholy: Olesʹ Ulianenko – Creativity, Contexts, Memories (2023). The authors of this book represent various visions and interpretations of the artistic works of one of the most iconic Ukrainian novelists of the 1990s and 2000s and mark an important stage in the formation of Ulianenko studies in Poland. Each researcher chooses his or her way of approaching Ulianenko’s artistic work. Sometimes these ways intersect, but each moves along his or her trajectory, ultimately revealing a multifaceted understanding of the writer’s work. The researchers consider the important problems of the moral crisis of man in the post-Soviet era, the sensuality of the heroes, which allows them to feel and understand the Other and perform a moral act, typology of characters, stylistic features of Ulianenko’s writing, and genre features of noir in his prose.